Effects of Subjective Norms and Environmental Mechanism on Green Purchase Behavior: An Extended Model of Theory of Planned Behavior - Yuhuan Xu; Jianguo Du; Muhammad Aamir Shafique Khan; Muhammad Aamir Shafique Khan; Shuai Jin; Mohsin Altaf; Farooq Anwar; Imran Sharif (Frontiers in Environmental Science, 2022)
Based on the theory of planned behavior, this paper presents a study on the core components of attitude, subjective norm, perceived behavior control, and introduces a moral emotional variable, namely environmental indebtedness, as the emotional factors in the attitude variable to explore the influencing factors and mechanism of consumer green purchase behavior. To examine the predictors of consumer green purchase behavior, data were collected from Chinese consumers and a total of 408 responses were considered valid. Through comparative analysis, it is found that environmental cognition, descriptive norm, and self-efficacy have a highly significant positive impact on green purchase intention, and self-efficacy was found the best predictor of intention. In addition to that, when environmental indebtedness, self-efficacy, controllability, and green purchase intention jointly have significant effects on green purchase behavior, environmental indebtedness has the best effect. This research offers significant contributions and provides decision-making recommendations.